Oczekiwania pracowników w stosunku do komunikacji wewnętrznej (studium przypadku) - Baranowska, Katarzyna (Employees' Expectations towards Inner Communication (Case Study), 2008)
The article concerns problems connected with inner communication in an organization, especially with the employees' expectations towards it. Fluent inner communication is one of the conditions of effective managing and market success of a company, although this aspect of managing the company is often underestimated by managers. This paper presents some results obtained from the study on employees' expectations towards inner-company communication, on the basis of X company. Those expectations should necessarily be taken into account by managers while working out the communication policy of the company. Data collected during the study indicates that realizing the employees' needed solutions allows to create an effective communication system which is adjusted to hard-working, motivated, engaged and loyal employees' team.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 445-453